NrCAM-deficient mice exposed to chronic stress exhibit disrupted latent inhibition, a hallmark of schizophrenia - Buhusi, Mona; Brown, Colten K.; Buhusi, Catalin V. (Frontiers in Behavioral Neuroscience, 2024)
The neuronal cell adhesion molecule (NrCAM) is widely expressed and has important physiological functions in the nervous system across the lifespan, from axonal growth and guidance to spine and synaptic pruning, to organization of proteins at the nodes of Ranvier. NrCAM lies at the core of a functional protein network where multiple targets (including NrCAM itself) have been associated with schizophrenia. Here we investigated the effects of chronic unpredictable stress on latent inhibition, a measure of selective attention and learning which shows alterations in schizophrenia, in NrCAM knockout (KO) mice and their wild-type littermate controls (WT). Under baseline experimental conditions both NrCAM KO and WT mice expressed robust latent inhibition (p=0.001). However, following chronic unpredictable stress, WT mice (p=0.002), but not NrCAM KO mice (F<1), expressed latent inhibition. Analyses of neuronal activation (cFos positive counts) in key brain regions relevant to latent inhibition indicated four types of effects: a main effect of single hit by genotype in IL cortex (p=0.0001), a single hit by stress in Acb-shell (p=0.031), a dual hit stress x genotype in mOFC (p=0.008), vOFC (p=0.020), and Acb-core (p=0.032), and no effect in PrL cortex (p>0.141). These results indicating a pattern of differential effects of genotype and stress support a complex stress x genotype interaction model and a role for NrCAM in stress-induced pathological behaviors relevant to schizophrenia and other psychiatric disorders.